Commercial cash crop production and households’ economic welfare: Evidence from the pulse farmers in rural China - Ji-liang MA; Fan LI; Hui-jie ZHANG; NAWAB Khan (Journal of Integrative Agriculture)
Whether promoting cash crop production can increase household welfare has long been the focus of the food policy debate. This study first investigated the determinants of household behavior in commercial pulse farming. It then examined how households’ commercial pulse production improves their economic welfare. We used a dataset of 848 households collected from 2018 to 2019 to estimate the determinants of household behavior in commercial pulse farming by the Heckman two-step model. The endogenous treatment regression (ETR) method was employed to examine the impact of commercial pulse farming on household economic welfare. The results showed that factors such as market purchase prices, agricultural technology services, farmers’ access to loans, and government subsidies promoted smallholders’ commercial pulse farming; production costs and perceptions of climate change risks constrained smallholders’ commercial pulse production. Overall, commercial pulse production has increased household farm income but there was a limited impact on household off-farm income. Our findings suggest that policies aiming to increase households’ cash crop production and market access could significantly improve the economic welfare of pulse farmers.